Sistem Pakar Diagnosa Penyakit Gigi Dan Mulut Pada Manusia Menggunakan Metode Forward Chaining Dan Certainty Factor Berbasis Web - Kurniawan, Imas; Isyriya, Laila; Tirtana, Arif (LPPM STIKI MALANG, 2021)
The understanding of oral and dental diseases in humans for the general public is still low. The community still relies on the expertise of an expert manually at a cost that is quite expensive. To minimize costs and facilitate consultations, a system that can predict the dental and oral disease that is currently being suffered is needed without having to go to the dentist and mouth first. An expert system for predicting dental and oral diseases is an application that can help the general public in diagnosing or predicting dental and oral diseases. So that the community can minimize costs and facilitate consultation. In this study, the forward chaining method was used to formulate rules and added the certainty factor (CF) method which was used to calculate the certainty value so that the determined results were clearer.TThe result of this expert system is a disease that has the greatest certainty value. From the figures obtained, it can be ascertained that the analysis using the interview method gets the most certainty results when compared to the other two methods.